(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Objectives: The aim of this study is to find that whether the medial surgical approach is beneficial to patients in term of radiological and functional outcome as compared to posterior approach for open reduction & internal fixation of displaced Supracondylar fractures of the humerus in children. Methods & material: It is a descriptive study conducted at department of Orthopaedic Surgery SKBZ/CMH Muzaffarabad from June 2020 to June 2021 on pediatric patients admitted with Gartland III supracondylar fractures of the humerus managed by open reduction & internal fixation using K-Wires via posterior & medial approach. Results: 113 children were included in this study. They were divided in to 2 groups. Group I managed with ORIF using medial approach and included 63 patients .Group II were managed with ORIF using posterior approach and included 50 cases. Flynn’s criteria was used to assess the cosmetic and functional outcomes of the ORIF. 97 % had satisfactory functional outcome in medial approach while 90 % gained satisfactory results in posterior approach group both approaches had almost same cosmetic outcome in term of regaining carrying angel. Mean surgery time was 40 ±15 minutes with medial approach white it was 75±16 that was markedly significant. Conclusion: Although different surgical approaches are used for ORIF of supracondylar fractures of humerus in children, but medial approach is safe, less time consuming and best scar acceptance than posterior and lateral approaches